Technological Infrastructure and the Implementation of Technological Strategies - Weiss, Andrew R.; Birnbaum, Philip H. (Management Science, 1989)
Technological change is an important strategic problem for many enterprises. Effectively implementing the technological aspects of a firm's strategy requires an understanding of the nature of the external infrastructure which supports technological change and the strategic capability to continuously interact with this infrastructure. After explaining why this infrastructure is important and how it is organized, we suggest the basic elements needed to implement a technological strategy successfully.